Food safety and quality awareness: promoting the WHO’s 5 keys safer food through community service program in Banjarsari Village, Kulon Progo Regency, Yogyakarta - Prabakusuma, Adhita Sri; Utami, Budi Barata Kusuma (Universitas Ahmad Dahlan, 2024)
Implementing food safety and quality practices at the household level is crucial to preventing foodborne illnesses and ensuring family health. This community service program focuses on promoting food safety and quality awareness in Banjarsari Village, Samigaluh District, Kulon Progo Regency, based on the World Health Organization’s (WHO) 5 Keys to Safer Food protocol. The program aimed to educate local communities on essential food handling practices to reduce foodborne illnesses and analyze the success factor prioritization of food safety and quality implementation. The community service activities encompassed conducting technical meetings, packaging all safe food items, executing the program, identifying the success factors for food safety and quality using the Analytical Hierarchy Process (AHP), and evaluation. The trainer explained in detail that the five keys to safer food include keeping clean, separating raw and cooked foods, cooking thoroughly, keeping food at safe temperatures, and using safe water and raw materials. According to the AHP analysis, factor 6 (choosing food processed for safety) had the highest weight (0.285) and the alternative of keep foods at safe temperature showed the most desirable values on the vertical axis (0.279). All participants expressed enthusiasm in this community service program and anticipated its continuation in the future.